PENGARUH MOTIVASI BELANJA HEDONIS TERHADAP PEMBELIAN IMPULSIF DARING PRODUK FESYEN ISLAMI - Jeffry Nugraha; Sudianto; Firdan Gusmara Kusumah; Hana Diana Maria; Adie Pamungkas; Puji Listiani (Bajang Institute, 2024)
Impulse buying is a purchase made without careful consideration or prior planning. This is the act of purchasing a product or service on a whim, often due to emotional or impulsive impulses, without carefully considering whether the purchase is truly necessary or meets actual needs or desires. Impulsive purchases are often triggered by factors such as attractive promotions, peer or environmental pressure, or a person's impulsiveness in making decisions. This research focuses on the influence of hedonic shopping motivation which is based on pleasure and external stimuli, one of which is the shop environment which can increase consumers' opportunities to make purchases. This research aims to see the influence of Hedonic Shopping Motivation on impulse buying among young women in Tasikmalaya. The population in this study were young women in Tasikmalaya with sample determination using incidental sampling techniques. The sample in this study amounted to 100 people. The measuring instruments used are the Hedonic Shopping Motivation scale, Store Atmosphere scale and Impulsive Buying. The results of data analysis show that Hedonic Shopping Motivation and store atmosphere have a significant effect on impulse buying. The results of the multiple regression analysis test show that, Hedonic Shopping Motivation and store atmosphere together have an influence of 50.7% on impulsive buying among young women in Tasikmalaya